SLEEP QUALITY AMONG INDEPENDENT OLDER PERSON IN COMMUNITY IN MALAYSIA - Akehsan Dahlan; Hanisha Haidzir; Mohamad Ghazali Masuri (Journal of Islamic, Social, Economics and Development, 2021)
Sleep is a basic physiological need. Good sleep is required for a person's overall health and well-being. Poor sleep quality often associated with increased risk of mortality, depression, lower cognitive performance, poor self-rated health status and lower quality of life. Epidemiology study indicates that older people often have poor sleep quality due to physical and psychological conditions. However, the information about sleep quality among the older person who lives in the community is inconclusive, especially among the independent older person. Hence, this study aimed to determine sleep quality among the independent older person who lives at home in the community. A cross-sectional study throughout Malaysia was conducted involving 335 older people from the community. The 19-item Malay version of the Pittsburgh Sleep Quality Index (PSQI-M) was used to assess sleep quality. There are 223 (66.6%) older persons who are having poor sleep quality (scores above 5 in PSQI-M), and the mean (SD) for sleep quality among older person with poor sleep quality is 9.00 (3.87). In addition, there was a significant correlation between age with sleep quality (r=-0.24, p<0.00) among older person in the community. Health care professionals should play an important role in improving sleep quality among older persons to promote health and well-being.